Alternative RNA Splicing in the Pathogenesis of Liver Disease - Webster, Nicholas J. G. (Frontiers in Endocrinology, 2017)
Non-alcoholic fatty liver disease (NAFLD) is becoming increasingly prevalent due to the worldwide obesity epidemic, and currently affects one third of adults or about 1 billion people worldwide. NAFLD is predicted to affect over 50% of the world’s population by the end of the next decade. It is the most common form of liver disease and is associated with increased risk for progression to a more severe form non-alcoholic steatohepatitis (NASH), as well as insulin resistance, type 2 diabetes mellitus, cirrhosis and eventually hepatocellular carcinoma. This review article will focus on the role of alternative splicing in normal liver physiology and dysregulation in liver disease.